Surface acoustic wave sensitivity on an exterenal mechanical or electrical bias - GAFKA, D. (Archives of Acoustics, 1994)
Using general rotationally invariant nonlinear electroelastic equations (energy balance equation and Gibbs function expansion) a derivation of constitutive equations for electroelastic media upon a mechanical or electrical bias has been presented. Bilinear constitutive relations for large quantities have been given and linear, but parametric, constitutive formulas for small-field variables have been derived in the reference or intermediate frame. Equations of motion and boundary conditions in the intermediate configuration required to solve the problem of SAW propagation are also reported. Basing on this theory, the velocity shifts of surface acoustic waves (SAW) for lithium niobate due to an external static stress or electric field are presented. Stress sensitivity is defined through six independent components of a second order symmetric tensor, and the electric field sensitivity is a vector of three components. Maps for different cuts of LiNbO3 and a different direction of SAW propagation have been computed. These maps can be used to find new cuts of lithium niobate which has large or zero sensitivity either on the stress or electric field. This could be useful for special applications of the LiNbO3 substrate in the technique of SAW devices.